Psocoptera (Insecta: Psocodea) of Iran with new records from caves - Mahmood Mehrafrooz Mayvan; Dilian Georgiev; Ľubomír Kováč (Journal of Insect Biodiversity and Systematics)
In this study, the psocids (Psocodea: 'Psocoptera') from caves and other ecosystems in Northeastern Iran were investigated during the years 2022 and 2024. Among them, Psyllipsocus ramburii Selys-Longchamps, 1872, and Lepinotus inquilinus Heyden, 1850, are new to the Iranian fauna. Additionally, all species identified in this study are newly recorded in North Khorasan and Khorasan-e Razavi provinces. Notably, this is the first report of Psocoptera from caves in Iran. In addition, we have compiled a list of psocid species of Iran based on the available literature until October 2024. A total of 22 species, belonging to 11 genera and 8 families of psocids have been reported from Iran. We made a brief analysis of the systematic, zoogeographical and ecological assignment of Iranian Procoptera. The suborder Troctomorpha, with 2 genera and 11 species, has the highest species count. From nine families recorded, the family Liposcelididae dominates, accounting for 11 species, or 50% of the total. The study includes bibliographical references and information on the global distribution of these species.